Water temperature modulation to prevent the South American rock mussel (Perna perna) from spawning during depuration - Felipe Matarazzo Suplicy; Robson V. de Souza; Giustino Tribuzi (Ocean and Coastal Research)
Sewage pollution is an increasing problem for Perna perna mussel farmers in Brazil, and there is an urgent need to adopt post-harvest treatments, such as depuration, to reduce the associated microbiological risks. However, depuration of this species has been discouraged by experiences showing that the animals usually spawn during this procedure, bringing difficulties for water treatment and making them lighter, weakened, and undesirable to be traded as a live product. This study aimed at developing a protocol to prevent mussels from spawning by modulating the water temperature during depuration. For one year (from 2021-07-07 to 2022- 06-29), market-size mussels harvested from the Brazilian southern coast were divided into groups of five and immersed during 50 hours in sets of experimental units (15 L acrylic aquariums) that emulated depuration tanks with different water temperatures (ranging from 8°C to 31°C). During this period, the experimental units were inspected nine times to check for spawning/spawned mussels. Analysis of the overall results showed that 21 (95.5%) out of the 22 assays resulted in mussels spawning and that this behavior was mostly recorded (80.3%) within the first 5:30 hours of the assays. The models developed (binary logistic regression) indicate that conditioning the depuration water to temperatures 5°C lower than those registered at the harvest site holds the potential to reduce the chances of spawning by more than 50%, and these chances drop to 8.2% when this difference reaches 10°C. Further studies are needed to show how reducing water temperature during depuration influences its efficiency in terms of pathogen reduction, aiming to define the best protocol to optimize microbial removal and minimize spawning.